Transformation of Yoga in Bali in the Era of Global Tourism - Ningrum Ambarsari; A.A. Ngr. Anom Kumbara; Nanang Sutrisno; Yang En Siem Evelyn (Universitas Udayana, 2025)
The dynamic interplay of globalization and spiritual tradition creates a cultural synthesis. This study examines the transformation of yoga practices in Bali as driven by global consumerism. Using a qualitative approach, the research draws on observations and interviews with studio founders in Ubud, Seminyak, and Denpasar. The study identifies four main areas: ideology, practices, management, and symbols. The results show a shift from spiritual practices to commercialized wellness routines. Western-run studios emphasize commercial interests through paid services and international branding, while local founders favor community-focused approaches. The adaptation of Hindu spiritual symbols reflects a move away from cultural specificity and raises concerns about the erosion of local heritage. This research contributes to understanding how Bali’s deep-rooted rituals integrate with modern yoga practices introduced by global tourism. It highlights resistance to homogenization while honouring both tradition and new practices, adapting to modern influences without losing unique original values.